Renewable Energy Sources in Poland in 2014-2023 and the Perspective of their Development until 2030. A Contribution to the Discussion - Świdyńska, Natalia (Olsztyn Economic Journal, 2024)
This article discusses the state of renewable energy sources (RES) in Poland, comparing it with the one in the EU-27. It has been emphasised that the Polish government is obliged carry out the EU policy, also in terms of energy targets. Thus, Poland is committed to achieving a 31.5% share of RES in all energy generation sources by year 2030. The aim of this study has been to determining the state of RES in Poland and determining the prospects for their further development based on it. The state of RES development in Poland has been determined on the basis of generally available statistical data (Poland Statistics GUS). Eurostat was the source of data pertaining to the European Union. According to preliminary data, in 2023, the share of RES in Poland was 27%, compared to 44% in the EU-27. Having determined the state of RES development in Poland, we were able to identify prospects for their future development. The prognosis made in this study substantiated the conclusion that the set target of 31.5% share of RES in all energy sources will not be achieved in Poland. The Polish economy is progressing in the right direction, and the RES share is increasing year to year, but the pace of this progress is too slow. Some ways of increasing the RES contribution to overall energy generation as well as certain obstacles to the growth of RES are implicated in this article. Attention has been drawn to the impact of the COVID-19 pandemic and war in Ukraine on the energy sector.